Eco-Friendly Adsorbent Derived From Palm Kernel Shell Waste As Activated Carbon For Crude Palm Oil (CPO) Purification - Umi Aisya’adah; Nasywa Zinta; Ailsa Putri Dyanti; Alfina Insani; Intan Lestari (CV. AFDIFAL MAJU BERKAH, 2026)
Indonesia, as the world’s largest palm oil producer, generates significant amounts of biomass waste, including palm kernel shells that remain underutilized. This study aims to develop eco-friendly activated carbon from palm kernel shell waste through carbonization and chemical activation using NaCl and ZnCl₂, and to evaluate its performance in Crude Palm Oil (CPO) purification. Carbonization was conducted at high temperatures under limited oxygen conditions, followed by chemical activation to enhance surface area and pore structure. The resulting materials were characterized using SEM, FTIR, XRD, and XRF to determine morphology, functional groups, crystal structure, and elemental composition. The adsorption performance was evaluated based on the reduction of free fatty acids, peroxide value, saponification value, and moisture content in CPO. The results indicate that ZnCl₂ activation produces a more developed pore structure and higher adsorption capacity compared to NaCl. This study demonstrates that palm kernel shell waste can be effectively utilized as a low-cost, sustainable, and environmentally friendly adsorbent, contributing to improved CPO quality and supporting circular economy practices in the palm oil industry.